EXTINCTION AND PERSISTENCE OF A STOCHASTIC SIS EPIDEMIC MODEL WITH VERTICAL TRANSMISSION, SPECIFIC FUNCTIONAL RESPONSE AND LEVY JUMPS. (2019) - NAIM, MOUHCINE; LAHMIDI, FOUAD; NAMIR, ABDELWAHED
No abstract available